2010
DOI: 10.1096/fj.09-149146
|View full text |Cite
|
Sign up to set email alerts
|

Signaling‐sensitive amino acids surround the allosteric ligand binding site of the thyrotropin receptor

Abstract: The thyrotropin receptor [thyroid-stimulating hormone receptor (TSHR)], a G-protein-coupled receptor (GPCR), is endogenously activated by thyrotropin, which binds to the extracellular region of the receptor. We previously identified a low-molecular-weight (LMW) agonist of the TSHR and predicted its allosteric binding pocket within the receptor's transmembrane domain. Because binding of the LMW agonist probably disrupts interactions or leads to formation of new interactions among amino acid residues surrounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 38 publications
7
44
0
Order By: Relevance
“…L587V mutation data of constitutive activation (Ref. 46 and Fig. 5) are consistent with the ␣-helix conformation in the second model.…”
Section: Methodssupporting
confidence: 79%
“…L587V mutation data of constitutive activation (Ref. 46 and Fig. 5) are consistent with the ␣-helix conformation in the second model.…”
Section: Methodssupporting
confidence: 79%
“…This allosteric mode of action may result from the inherent property of small molecules, including their small size and hydrophobic nature. However, it has been shown that the TSHR contains clusters of residues with allosteric potential encompassing signaling-sensitive amino acids within the helices of the TMD (21). To determine if our lead molecules were allosteric modulators, as expected, we tested their receptorstimulating activity on a chimeric receptor in which the major part of its ectodomain consists of the LHR sequence fused to the native human TSHR TMD.…”
Section: Pk Studiesmentioning
confidence: 99%
“…SMLs by virtue of their small size can permeate the cell and dock with polar and nonpolar residues in the TMD region and exert their effects in an allosteric manner (21). In the case of the TSHR, the different transmembrane helices and intracellular and extracellular loops connecting these helices have been studied extensively for activating and inactivating mutations (22), which are the ''hot-spots'' in the receptor, having been found in human pathological conditions (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSHr is a G protein-coupled receptor that transfers extracellular signals mainly by the TSH/TSHr-caMP-PKa and TSH/TSHr-Plc-iP3 pathways (18,19). The mechanism by which TSH regulates the expression and activity of niS through the cAMP-PKA pathway has been partially clarified by several studies.…”
Section: Introductionmentioning
confidence: 99%